The Implementation of Using Flashcard as a Media to Improve Students’ Vocabularies Mastery at 8 Grade in SMP Negeri 1 Tondano - Kalaudi, Sindi Vanessa; Liando, Nihta V. F; Rorimpandey, Rinny S (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
Abstract: The purpose of this research was to know whether the implementation of using flashcard as a media to improve students’ vocabularies mastery. The researcher conducted at the 8th grade students of SMP Negeri 1 Tondano, which consist of 20 students for the 2023/2024 academic year. This research is quantitative research using a pre-experimental design which is only carried out with a pre-test and post- test in one class. Researcher collect data starting from the pre-test or before providing treatment and post-test after providing treatment. Based on the findings,it shows that before being given treatment, students got poor grades on the pre-test but on the post-test, or after the researcher gave treatment, the scores obtained by students exceeded the pre-test so that students had better grades than before (pre - test). The pre-test score was 55.70 and the post test score was 83.25, which means the post test score was higher than the pre-test score. And the significant value is 0.000(<)0.05, which means smaller than the alpha value. So, the researcher concluded that the implementation of using flashcard media can improve students'vocabulary mastery.